Efektivitas Konseling Kelompok Dengan Teknik Home Work Assigment Untuk Meningkatkan Self Efficacy Anak Di Panti Asuhan Cahaya Kemuning Palembang - Lestari, Edya Dwi; Razzaq, Abdur; Noviza, Neni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
The purpose of this study was to determine the self-efficacy description of children before being given group counseling using the home work assignment technique and to determine the effectiveness of group counseling using the home work assignment technique to increase self-efficacy in children. The approach used is qualitative with quantitative research methods. The study population is 14 people. The sampling technique used is purposive sampling, namely the method of determining respondents based on certain criteria so that the research sample is 10 people. Data collection techniques using observation, documentation and questionnaires. The results showed that the self-efficacy of the orphans before being given group counseling with the home work assignment technique was 36.9 in the medium category and after being given group counseling with the home work assignment technique 67.2 in the medium category. Then the results of the Wilcoxon signed rank test obtained Zcount of 2.803 and Ztable of 1.96 with a significant level of 5% so Zcount ≥ Ztable. Thus Ha is accepted and Ho is rejected. These results indicate that the self-efficacy of children at the Cahaya Kemuning Orphanage can be increased through group counseling with the home work assignment technique. The purpose of this study was to determine the self-efficacy description of children before being given group counseling using the home work assignment technique and to determine the effectiveness of group counseling using the home work assignment technique to increase self-efficacy in children. The approach used is qualitative with quantitative research methods. The study population is 14 people. The sampling technique used is purposive sampling, namely the method of determining respondents based on certain criteria so that the research sample is 10 people. Data collection techniques using observation, documentation and questionnaires. The results showed that the self-efficacy of the orphans before being given group counseling with the home work assignment technique was 36.9 in the medium category and after being given group counseling with the home work assignment technique 67.2 in the medium category. Then the results of the Wilcoxon signed rank test obtained Zcount of 2.803 and Ztable of 1.96 with a significant level of 5% so Zcount ≥ Ztable. Thus Ha is accepted and Ho is rejected. These results indicate that the self-efficacy of children at the Cahaya Kemuning Orphanage can be increased through group counseling with the home work assignment technique.